Navigating Security Dilemma: South Korea’s Space Program during President Moon Jae-In’s Administration (2017-2022) - Rahmah, Himmalia Dewi Alya (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
Research about South Korean space programs is quite challenging to find among other spacefaring nations such as the US, Russia, China, and even India. It contrasts with its achievements in space missions and programs over the past five years, particularly during President Moon Jae-in’s leadership. For instance, it finally launched its domestically built space launch vehicle, KSLV-II. South Korean space programs are especially interesting when juxtaposed with the volatility of the Korean Peninsula. Nonetheless, analysis of systemic constraints that limit South Korean space programs to pursue military-focused space programs is greatly overlooked. Hence, this research asks why South Korea avoids developing security/military-focused space programs and instead opts for peaceful space programs amid the presence of space threats in the region. This research uses two theoretical frameworks to answer the question: (1) the middlepowermanship approach by a middle power in a security dilemma, (2) post-Cold War space programs, and the logic of space economy. Two hypotheses are presented: (1) South Korea employs middlepowermanship by facilitating orderly change in dealing with the space threat in the Korean Peninsula (2) In manifesting the peaceful approach, South Korea is thus focusing on improving its civil space program, that is, the space economy to prevent worsening the tension in the region.Keywords: South Korea, space programs, space threat, middle power, space economyDibandingkan dengan negara spacefaring lainnya seperti Amerika Serikat, Rusia, Tiongkok, bahkan India, penelitian mengenai program keantariksaan Korea Selatan cukup sulit ditemukan. Hal ini kontras dengan prestasi yang telah dicapai oleh Korea Selatan dalam kurun waktu lima tahun terakhir, khususnya pada era Presiden Moon Jae-in. Misalnya, keberhasilan peluncuran KSLV-II sebagai kendaraan peluncur antariksa pertama yang secara keseluruhan diproduksi secara domestik. Menilik lebih lanjut mengenai program keantariksaan Korea Selatan semakin menarik jika dikontraskan dengan ketidakstabilan Semenanjung Korea. Namun demikian, analisis hambatan sistemis yang membatasi opsi Korea Selatan untuk menempuh program keantariksaan yang berfokus pada bidang militer cenderung tidak banyak dibahas. Oleh karena itu, penelitian ini mempertanyakan mengapa Korea Selatan menghindari program keantariksaan yang berfokus pada aspek militer, dan justru memilih trajektori damai di tengah keberadaan ancaman-ancaman keantariksaan di kawasan. Untuk menjawab pertanyaan tersebut, ada dua kerangka teori yang digunakan (1) pendekatan middlepowermanship oleh middle power dalam dilema keamanan, (2) program keantariksaan pasca Perang Dingin, dan logika ekonomi keantariksaan. Dua hipotesis kemudian muncul, (1) Korea Selatan menggunakan middlepowermanship dengan memfasilitasi perubahan yang teratur guna mengatasi ancaman keantariksaan di Semenanjung Korea, (2) dalam memanifestasikan pendekatan damainya, Korea Selatan kemudian fokus dalam meningkatkan program keantariksaan sipilnya, yakni melalui ekonomi keantariksaan guna mencegah memburuknya ketegangan di kawasan.Kata-kata Kunci: Korea Selatan, program keantariksaan, ancaman keantariksaan, middle power, ekonomi keantariksaan